Cotidiano da residência terapêutica - Silva, Dayse Andrade Bispo (2012)
Therapeutic Residences (RT) are one of the main instruments to insert the madness theme in our society, they are houses where (mainly) former psychiatric hospital patients live. This research proposes to look how an everyday life of these residences raises vectors for production of subjective. In order to do so, we initially describe the history of living for madness in the West, from their freer movements until their enclosure; followed by the Brazilian context, experiences and political movements that initiated our current Mental Health Policy; up until its history and current setting of RT, especially in the city of São Paulo. We discuss the concept of everyday life using references from Pichon-Rivière and Michael de Certeau, and the concept of production of subjective from Felix Guattari. We performed Participant Observation for a six months period in a male RT, in the city of São Paulo. This observation followed both their everyday life inside the house and their outdoors activities. Our methodological reference is Institutional Analysis, which allowed us to follow and draw some clippings of this RT s everyday life through analyser-scenes. These scenes were analysed by some vectors of subjectivity, specifically those indicated in the psychosocial rehabilitation perspective, by F. Rotelli and B. Saraceno: reconstructions of meaning/values, of time, of responsibility and the social reentry. The concepts of reside and dwell were added as an analyses operators. This singular experience points to important reflections about RTs: its value in their psychosocial rehabilitation, principally in the social circulation, autonomy production and the creation of new ways to live. It is also worth highlight the difficulties to expand this house/service from the low involvement by the local manager associated with the financial barriers that this service requires and the lack of a national campaign about the changes in Mental Health